Salicylate and glutamate mediate different Cd accumulation and tolerance between Brassica napus and B. juncea. (April 2022) - Zhang, Zhong-Wei; Deng, Zong-Lin; Tao, Qi; Peng, Hong-Qian; Wu, Fan; Fu, Yu-Fan; Yang, Xin-Yue; Xu, Pei-Zhou; Li, Yun; Wang, Chang-Quan; Chen, Yang-Er; Yuan, Ming; et al.
Abstract: Most hyperaccumulator plants have little economic values, and therefore have not been widely used in Cd-contaminated soils. Rape species are Cd hyperaccumulators with high economic values. Black mustard seed ( Brassica juncea ) has a higher accumulation ability and a higher tolerance for Cd than oilseed rape ( Brassica napus ), but its biomass is relatively low and its geographical distribution is limited. However, it is unknown why B. juncea (Bj) is more tolerant to and accumulates more Cd than B. napus (Bn). Here, we found that the differences in Cd accumulation and tolerance between the two species is mainly because Bj plants have higher levels of salicylic acid and glutamic acid than Bn plants. Exogenous salicylate and glutamate treatments enhanced Cd accumulation (salicylate + glutamate co-treatment doubled Cd accumulation level in Bn seedlings) but reduced oxidative stresses by increasing glutathione biosynthesis and activating phytochelatin-based sequestration of Cd into vacuoles. Our results provide a new idea to simultaneously improve Cd accumulation and Cd tolerance in B. napus . Graphical abstract: Image 1 Highlights: Brassica napus has a high economic value but a low Cd accumulation than B. juncea. B. juncea has higher levels of salicylate (SA) and glutamate (Glu) than B. napus. SA and Glu enhanced Cd accumulation by activating Cd sequestration into vacuoles. SA and Glu reduced oxidative stresses by increasing reduced glutathione. SA and Glu enhanced Cd accumulation and tolerance simultaneously.